Only Only ? An Experimental Window on Exclusiveness - Jayez, Jacques; van Tiel, Bob (Proceedings of the Amsterdam Colloquium, 2011)
In a recent book, David Beaver and Brady Z. Clark argue that only does not presuppose the proposition in its scope, contrary to the ‘standard’ theory articulated in (Horn 1969), and propose a new semantic representation for only. Their rejection of the standard theory is based on linguistic observations and a survey test. We adduce new experimental evidence suggesting that (i) dropping the standard theory altogether might be too radical a move and (ii) the very idea that the behaviour of only derives from a combination logical form + context, even if it proves ultimately adequate, cannot be taken as granted.